ANALISIS KOMPETENSI TUTOR PENDIDIKAN KESETARAAN PROGRAM PAKET B DI PROVINSI JAWA TIMUR - Moh. Muzaqi; Dwi Sudarmanto; Widya Ayu P; Yuni Ekawati (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2008)
As an educator in non-formal education, a tutor is demanded to have knowledge and competence that are suitable with his or her function and duty. This research is conducted to find out the competence of Package B tutors in doing a learning process in equivalency education. The research using assessment done by tutor, manager, and Package B students indicates that functional, social, personal, pedagogy and andragogy competence of tutors is in good category.